Fluorescent material based on tetraphenylimidazole as well as synthesis method and application of fluorescent material
Through the technical application areas extracted in the patent specification, the tetraphenylimidazolium fluorescent material IZ-F has achieved acid-induced fluorescence color change in the solid state, solving the problem of fluorescence quenching in the solid state of existing materials, and realizing efficient pH sensing and acid-base detection.
Patent Information
- Application Number
- CN202511313588.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2025-12-05
AI Technical Summary
Existing acid-induced fluorescent color-changing materials exhibit fluorescence quenching and insensitive response in the solid state, making them difficult to apply to efficient pH sensing and acid-base detection.
A tetraphenylimidazolium-based fluorescent material IZ-F was designed. By constructing a cyanostilbene structure to extend the π-conjugated structure, aggregation-induced emission enhancement properties were achieved, and the material exhibited obvious acid-induced fluorescence color change properties in solid powder form.
Material IZ-F exhibits significant fluorescence color-changing properties in solid powder form in response to acidic substances, with fluorescence clearly switching between yellow and cyan-blue. It is suitable for pH sensors, acid-base switches, and acid-base detectors, avoiding the fluorescence quenching problem of traditional materials, and is highly sensitive and efficient.
Smart Images

Figure CN121064103A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of organic fluorescent materials, and particularly relates to a fluorescent material based on tetraphenyl imidazole and a synthesis method and application thereof. BACKGROUND
[0002] Organic fluorescent materials have attracted much attention due to their strong structural modifiability, easy controllability of light-emitting wavelength band, and wide application fields. Acid-induced fluorescent color-changing materials are a special kind of organic fluorescent materials, the molecules of which can change their fluorescent properties with changes in acid-base conditions. This property makes them useful for monitoring changes in acid-base conditions in solution or air environment, and has important practical application value.
[0003] Most acid-induced fluorescent color-changing materials contain groups (such as amino, imidazole, pyridine, etc.) that can interact with protons in their molecular structures. The combination of these groups with protons can cause changes in the molecular structure of the compound, which in turn causes significant changes in the fluorescence spectrum. Based on this property, pH sensors, acid-base switches, and acid-base detectors can be developed.
[0004] Among the many chromophoric groups, the tetraphenyl imidazole group has a certain conjugated structure and exhibits a twisted non-planar feature. In dilute solution, it can exhibit excellent blue fluorescence emission performance, and has high fluorescence quantum yield and good spectral stability. At the same time, the imidazole group, as a typical basic functional group, can combine with acidic substances, causing rearrangement of the intramolecular electronic structure and changes in the spatial configuration, ultimately causing significant changes in its photophysical properties, thereby realizing its detection function.
[0005] Therefore, using tetraphenyl imidazole as the parent structure and constructing a cyanodiphenylstyrene structure to regulate the charge flow within the molecule, a new type of organic fluorescent material is designed, and the internal relationship between its photophysical properties and spatial structure is explored, which has important guiding significance for synthesizing new organic fluorescent materials with excellent performance. SUMMARY
[0006] The purpose of the present application is to provide a fluorescent material based on tetraphenyl imidazole and a synthesis method and application thereof. The material exhibits aggregation-induced emission enhancement (AIEE) properties, exhibits strong fluorescence emission characteristics in the solid powder state, and exhibits obvious acid-induced fluorescent color-changing properties to acidic substances, realizing the conversion of fluorescence between yellow and cyan blue, and can be applied in the fields of pH sensors, acid-base switches, and acid-base detectors.
[0007] To solve the above technical problems, the technical solution adopted by the present application is to provide a fluorescent material based on tetraphenyl imidazole, which has the following structure:
[0008]
[0009] The tetraphenyl imidazole-based fluorescent material of the present application effectively expands the pi conjugated structure of the molecule by constructing a cyanodiphenyl styryl group on the tetraphenyl imidazole parent body, and finally obtains a new organic fluorescent material with AIEE properties and strong fluorescence emission in a solid powder state. Its core characteristics are: in a solid powder state, it shows obvious acid-induced fluorescence color change properties to acidic substances, and the fluorescence can be stably converted between yellow and cyan blue, which lays a foundation for its application in acid-base response products, and can be applied in the fields of pH sensors, acid-base switches and acid-base detectors.
[0010] The present application also provides a synthesis method of the tetraphenyl imidazole-based fluorescent material, which disperses the aldehyde group-containing tetraphenyl imidazole derivative IZ-1, p-fluorobenzeneacetonitrile and potassium tert-butoxide in anhydrous ethanol, heats to reflux until the reaction is completed, and then purifies by silica gel column chromatography to obtain the tetraphenyl imidazole-based fluorescent material IZ-F.
[0011] Further, the molar ratio of the aldehyde group-containing tetraphenyl imidazole derivative IZ-1 to p-fluorobenzeneacetonitrile is 1:(1.2-1.5).
[0012] Further, the molar ratio of the potassium tert-butoxide to the aldehyde group-containing tetraphenyl imidazole derivative IZ-1 is (1.2-1.5):1.
[0013] Further, the addition amount of ethanol is based on the aldehyde group-containing tetraphenyl imidazole derivative IZ-1, and 20-30 mL of anhydrous ethanol is added for 1 mmol of the aldehyde group-containing tetraphenyl imidazole derivative IZ-1.
[0014] The synthesis method of the present application is to synthesize the target molecule IZ-F by Knoevenagel condensation reaction of the aldehyde group-containing tetraphenyl imidazole derivative IZ-1 and the p-fluorobenzeneacetonitrile under alkaline conditions, the raw materials are simple and easy to obtain, the synthesis route is simple, and the conditions are mild. By constructing a cyanodiphenyl styryl structure into the tetraphenyl imidazole parent structure, a fluorescent material with acid-induced fluorescence color change property is obtained.
[0015] Since the tetraphenyl imidazole-based fluorescent material IZ-F has obvious acid-induced fluorescence color change property (the fluorescence peak position can be blue-shifted from 560 nm (yellow fluorescence) to 468 nm (cyan fluorescence) with a blue-shift range of 92 nm) in the solid powder state, the application of the above-mentioned tetraphenyl imidazole-based fluorescent material IZ-F in a pH sensor, an acid-base switch or an acid-base detector is also provided, wherein the pH sensor utilizes the acid-induced fluorescence color change property of the fluorescent material IZ-F to monitor the pH value of the environment by the fluorescence color and peak position change; the acid-base switch realizes the regulation of the "on-off" state based on the reversible conversion of the fluorescence color of the fluorescent material IZ-F between yellow and cyan blue; and the acid-base detector detects the presence and concentration change of acidic substances in the solution or air by utilizing the acid-induced fluorescence color change property of the fluorescent material IZ-F.
[0016] Compared with the prior art, the application has the following beneficial effects:
[0017] In terms of synthesis, the raw materials (compound IZ-1, p-fluorobenzyl cyanide, potassium tert-butoxide, etc.) are easy to obtain, the synthesis route can be completed by only dispersing the raw materials in anhydrous ethanol, heating and refluxing and then purifying through a silica gel column, the reaction conditions are mild (without extreme temperature and pressure or special catalyst), and the yield of the target product IZ-F is stable (up to 62.6%); in terms of performance, the fluorescent material IZ-F has both the aggregation-induced emission enhancement (AIEE) property and the obvious acid-induced fluorescence color change property, which not only avoids the defect of the aggregation-caused quenching (ACQ) of traditional organic fluorescent materials through J-type stacking (intermolecular C-H···F hydrogen bond and C-H···π interaction) to realize strong solid-state fluorescence emission, but also can quickly respond to acidic substances in the solid powder state to clearly convert the fluorescence between yellow (560 nm) and cyan blue (468 nm) (with a peak position blue-shift of 92 nm) with high color contrast and sensitive response; in terms of application, the material can be directly applied to the pH sensor, the acid-base switch and the acid-base detector without secondary modification, which simplifies the application process, the design idea of constructing the cyanodiphenylstyrene structure based on the tetraphenyl imidazole also provides an effective reference for the research and development of multifunctional organic fluorescent materials, and enriches the organic fluorescent material system. BRIEF DESCRIPTION OF DRAWINGS
[0018] Figure 1 It is the nuclear magnetic resonance hydrogen spectrum of the tetraphenyl imidazole-based fluorescent material IZ-F of the application.
[0019] Figure 2 It is the nuclear magnetic resonance carbon spectrum of the tetraphenyl imidazole-based fluorescent material IZ-F of the application.
[0020] Figure 3 It is the stacking structure diagram of the tetraphenyl imidazole-based fluorescent material IZ-F of the application.
[0021] Figure 4 This invention presents the UV-Vis absorption and fluorescence spectra of the tetraphenylimidazolium-based fluorescent material IZ-F in different solvents.
[0022] Figure 5 This invention relates to the UV-Vis absorption and fluorescence spectra of the tetraphenylimidazolium-based fluorescent material IZ-F during the aggregation process.
[0023] Figure 6 This invention relates to the acid-induced fluorescence color-changing spectrum of the tetraphenylimidazolium-based fluorescent material IZ-F. Detailed Implementation
[0024] The present invention will be further described below with reference to preferred embodiments. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed herein.
[0025] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0026] Unless otherwise specified, the experimental methods described in the following examples are conventional methods.
[0027] A tetraphenylimidazolium-based fluorescent material, IZ-F, has the following structural formula:
[0028]
[0029] The specific synthesis method is as follows:
[0030] A tetraphenylimidazolium derivative containing an aldehyde group, IZ-1 (1.00 g, 1.83 mmol), p-fluorophenylacetonitrile (0.37 g, 2.74 mmol), and potassium tert-butoxide (0.31 g, 2.74 mmol) were dispersed in 50 mL of ethanol. The mixture was stirred to ensure thorough dispersion, and the solution was heated to reflux. Thin-layer chromatography (TLC) was used to monitor the reaction until completion. After cooling to room temperature, insoluble impurities were removed by filtration, and the solution was purified by silica gel column chromatography (petroleum ether: CH2Cl2 = 1:1, V / V). The target fraction was collected, and the solvent was removed under reduced pressure to obtain a yellow solid product, IZ-F (0.76 g, 1.14 mmol), with a yield of 62.6%. Its structural characterization is as follows. Figure 1 and Figure 2 As shown, FT-IR (KBr, cm -1): 3049, 2969, 2927, 2892, 2214, 1610, 1561, 1529, 1510, 1482, 1447, 1353, 1269, 1237, 1206, 1159, 1076, 1006, 957, 835, 776, 735, 716, 698, 531. 1 1H NMR (CDCl3, 400 MHz) δ: 7.94 (d, J = 8.04 Hz, 2H), 7.68 - 7.65 (m, 4H), 7.60 (d, J = 7.44 Hz, 2H), 7.54 (d, J = 8.44 Hz, 2H), 7.48 (s, 1H), 7.30 (d, J = 8.96 Hz, 2H), 7.26 - 7.22 (m, 5H), 7.17 - 7.12 (m, 7H), 6.52 (d, J = 9.00 Hz, 2H), 3.32 (q, J = 7.04 Hz, 4H), 1.12 (t, J = 7.12 Hz, 6H). 13 13C NMR (CDCl3, 101 MHz) δ: 163.33 (d, J C-F = 251.5 Hz), 147.92, 147.71, 141.79, 141.44, 139.11, 138.08, 137.59, 134.84, 132.99, 131.31, 131.09, 130.67 (d, J C-F = 3.2 Hz), 130.19, 129.94, 129.90, 129.16, 128.46, 128.20, 127.98 (d, J C-F = 8.5 Hz), 127.89, 127.55, 127.52, 127.48, 126.49, 118.05, 117.20, 116.30 (d, J C-F = 22.1 Hz), 111.02, 110.71, 44.33, 12.70. ESI-MS: m / z = 665.3074 ([M + H] + ), calcd for C 46 H 38 N4F + = 665.3081 ([M + H] + ).
[0031]
[0032] Performance Test
[0033] A yellow single crystal was obtained by dissolving 15 mg of the above-synthesized compound IZ-F in 5 mL of dichloromethane, filtering out impurities, transferring the filtrate to a test tube, slowly adding a small amount of ethanol to cover the surface, and slowly evaporating the solvent at room temperature. Figure 3 As can be seen from the stacking structure shown in the figure, the IZ-F crystal is monoclinic, the space group is Pī, the IZ-F molecules are stacked through intermolecular hydrogen bonds (C-H···F) and C-H···π interactions to form a three-dimensional network structure, and the stacking mode is J-type. This stacking mode can effectively weaken the intermolecular π-π stacking interaction, reduce the non-radiative transition path, and make IZ-F exhibit strong fluorescence emission characteristics in the solid powder state.
[0034] From Figure 4 The UV-visible absorption spectra and fluorescence spectra in different solvents can clearly show that in different organic solvents (c = 1.0 × 10 -5 mol L -1 ), the maximum absorption peak of compound IZ-F is stable at about 325 nm, and the molar absorption coefficient is more than 4.51 × 10 4 L / (cm·mol), which fully shows that this transition process belongs to the transition allowed type. It is particularly worth mentioning that with the increase of the solvent polarity, the absorption peak does not shift significantly, which reveals that the compound is relatively small in the influence of the solvent polarity in the ground state and the excited state, and it is inferred that this absorption peak may belong to the intramolecular π-π* transition. Further analysis of the fluorescence spectrum shows that the compound exhibits relatively obvious fluorescence emission characteristics in the low-polarity solvent. Specifically, in dichloromethane solvent, the fluorescence emission intensity reaches the peak, and the emission peak is located at 513 nm, showing greenish blue fluorescence. However, with the gradual increase of the solvent polarity, the fluorescence intensity is significantly weakened, and an obvious double-peak emission phenomenon appears, and the emission peaks are located at about 430 nm and 526 nm. The emission peak near 430 nm may be derived from the tetraphenyl imidazole group in the molecular structure; and the emission peak at 526 nm may be closely related to the α-cyanostilbene structure.
[0035] From Figure 5UV-Vis absorption and fluorescence spectra of the aggregation process can be seen that when the water content of the benign solvent tetrahydrofuran is less than 60%, the molar absorption coefficient of compound IZ-F remains relatively stable and the absorption peak position is also stable, which indicates that under this condition, the compound still exists in the form of single molecule and no significant aggregation phenomenon occurs. However, as the water content continues to rise, the absorption intensity begins to gradually weaken, which implies that the accumulation between molecules begins to occur, because as the molecules aggregate, the effective particle number in the solution decreases, and a significant lifting of the absorption tail line can be seen, which is due to the Mie scattering effect of the aggregated particles. Corresponding to the fluorescence spectrum, it can be seen that when the compound is below 60% water content, it shows weak fluorescence emission, and as the molecules aggregate, the fluorescence intensity begins to increase rapidly, and the fluorescence peak position is significantly red-shifted compared to the single molecule state, and reaches a maximum at 90%. However, when the water content continues to increase, the fluorescence intensity begins to decrease, which is mainly due to the compound sedimentation phenomenon caused by excessive aggregation, resulting in a sharp decrease in the number of effective light-emitting molecules in the solution. This phenomenon shows that compound IZ-F is a typical AIEE material. For the AIEE mechanism, through single crystal packing, it can be found that the compound molecules mainly construct a three-dimensional structure through C-H···F hydrogen bonds and C-H···π weak interactions, showing a unique twisted spatial configuration. This packing mode effectively avoids the fluorescence quenching effect caused by traditional π-π stacking, laying a structural foundation for efficient fluorescence emission. At the same time, the intermolecular forces form a rigid environment that significantly inhibits the free rotation of intramolecular single bonds, blocking the non-radiative transition channel from the dynamic level, so that the excited state energy can be efficiently released through radiative transition. More noteworthy is that the compound adopts a J-type aggregation packing mode, which not only optimizes the degree of electron cloud overlap, but also further amplifies the fluorescence emission intensity through intermolecular electronic coupling effect. Under the synergistic action of the above factors, the compound therefore exhibits fluorescence intensity enhancement and peak redshift.
[0036] From Figure 6 The acid-induced fluorescence color change fluorescence spectrum can be seen that by acidifying the compound IZ-F powder, it is found that the fluorescence emission peak of the original sample is 560 nm, showing yellow fluorescence emission, and the quantum yield is 12.69%. When compound IZ-F is placed in a saturated hydrochloric acid vapor atmosphere, the fluorescence peak quickly blue shifts to 468 nm, which is blue-green light emission, and the fluorescence peak blue shifts by 92 nm. Combined with the chemical structure of the compound, it can be known that because the imidazole group exhibits basic properties, after combining with acidic substances, it has strong electron-withdrawing properties, causing the rearrangement of the intramolecular electronic structure and the change of the spatial configuration, so the fluorescence characteristics of the imidazole group are exhibited. From the above data, it can be seen that material IZ-F in the solid powder state exhibits obvious acid-induced fluorescence color change properties to acidic gas, and the main reason is the change of the material structure.
[0037] Due to the special photophysical properties, the material can be applied in the fields of pH sensor, acid-base switch and acid-base detector: first, IZ-F has significant and sensitive acid-induced fluorescence color change performance, in the solid powder state, the initial fluorescence emission peak is 560 nm (yellow, quantum yield 12.69%), after being placed in saturated hydrochloric acid vapor, the fluorescence peak can quickly blue shift to 468 nm (cyan), the peak blue shift amplitude is 92 nm, the fluorescence color change is clear and identifiable, which can directly reflect the existence of acidic substances and the change of acid-base environment, and provide clear signal for acid-base detection and state switching; second, IZ-F has the property of aggregation-induced emission enhancement (AIEE), in the aggregated state (such as tetrahydrofuran-water system with water content > 60%) and solid powder, due to the J-type stacking formed by intermolecular C-H···F hydrogen bond and C-H···π interaction, the problem of aggregation-caused quenching (ACQ) of traditional fluorescent materials is effectively avoided, strong fluorescence emission in solid state is realized, the stability and intensity of fluorescence signal in device application (such as solid components of pH sensor and acid-base switch) are ensured, and detection error caused by weak signal is avoided.
[0038] The above only describes the preferred embodiments of the present application. It should be noted that for those skilled in the art, some adjustments of raw material ratio can be made without departing from the principles of the present application, which should also be considered as falling within the protection scope of the present application.
Claims
1. A tetraphenyl imidazole-based fluorescent material, characterized by, The specific structural formula is:
2. The method of synthesis of tetraphenyl imidazole based fluorescent material as claimed in claim 1, wherein: The aldehyde group-containing tetraphenyl imidazole derivative IZ-1, p-fluorobenzyl cyanide and potassium tert-butoxide are dispersed in anhydrous ethanol, heated to reflux until the reaction is completed, and then purified by silica gel column chromatography to obtain the tetraphenyl imidazole-based fluorescent material IZ-F, wherein the aldehyde group-containing tetraphenyl imidazole derivative IZ-1 has the structural formula:
3. The method of synthesis of claim 2, wherein: The molar ratio of the aldehyde group-containing tetraphenyl imidazole derivative IZ-1 to p-fluorobenzyl cyanide is 1:(1.2-1.5).
4. The method of synthesis of claim 2, wherein: The molar ratio of potassium tert-butoxide to the aldehyde group-containing tetraphenyl imidazole derivative IZ-1 is (1.2-1.5):
1.
5. The method of synthesis of claim 2, wherein: The amount of ethanol added is 20-30 mL of anhydrous ethanol per 1 mmol of the aldehyde group-containing tetraphenyl imidazole derivative IZ-1.
6. The application of the tetraphenyl imidazole-based fluorescent material of claim 1 in a pH sensor.
7. The application of the tetraphenyl imidazole-based fluorescent material of claim 1 in an acid-base switch.
8. The application of the tetraphenyl imidazole-based fluorescent material of claim 1 in an acid-base detector.